Comparative effectiveness of empagliflozin versus dapagliflozin in adults with metabolic dysfunction-associated steatotic liver disease - Wu, Jheng-Yan; Tu, Yu-Kuan; Kuo, Chia-Chih; Liu, Mei-Yuan; Hsu, Wan-Hsuan; Tsai, Ya-Wen; Liu, Ting-Hui; Huang, Po-Yu; Chuang, Min-Hsiang; Hung, Kuo-Chuan; Yu, Tsung; Liao, Kuang-Ming; et al. (Frontiers in Endocrinology, 2025)
BackgroundSodium-glucose co-transporter-2 inhibitors (SGLT2is) show promise in treating metabolic dysfunction-associated steatotic liver disease (MASLD). However, the relative efficacy of different SGLT2is remains unclear. We aimed to compare the clinical effectiveness of empagliflozin versus dapagliflozin in adults with MASLD.MethodsUsing the TriNetX database, we conducted a retrospective cohort study of adults with MASLD who were newly prescribed either empagliflozin or dapagliflozin between January 2013 and September 2024. After propensity score matching, we compared 13,274 patients in each group. The primary outcome was a composite of all-cause hospitalization, all-cause mortality, major adverse cardiovascular events (MACEs), major adverse kidney events (MAKEs), and decompensated hepatic events. Secondary outcomes included each individual component of the primary outcome.ResultsEmpagliflozin was associated with a lower risk of primary composite outcomes compared to dapagliflozin (HR, 0.84; 95% CI, 0.80-0.88). This benefit was consistent across most subgroups, including sex, presence of liver cirrhosis, heart failure, T2DM, and chronic kidney disease. Significant interactions were observed for age groups (p=0.04) and borderline for BMI categories (p=0.06). Empagliflozin also showed lower risks for all-cause hospitalization (HR, 0.84; 95% CI, 0.79-0.88), all-cause mortality (HR, 0.79; 95% CI, 0.66-0.96), MACE (HR, 0.88; 95% CI, 0.78-0.99), and MAKE (HR, 0.63; 95% CI, 0.47-0.86), but no difference in decompensated hepatic events (HR, 1.01; 95% CI, 0.81-1.27).ConclusionsIn patients with MASLD, empagliflozin was associated with better clinical outcomes compared to dapagliflozin, particularly in reducing cardiovascular and renal events, hospitalizations, and mortality.